2012
DOI: 10.1158/1078-0432.ccr-11-2073
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Temozolomide and Dose-Escalated Intensity-Modulated Radiation Therapy in Newly Diagnosed Glioblastoma

Abstract: Purpose To determine the maximum tolerated dose (MTD) of radiation (RT) with concurrent temozolomide (TMZ) in patients with newly diagnosed glioblastoma (GBM), to estimate their progression free (PFS) and overall survival (OS), and to assess the role of 11C methionine PET (MET-PET) imaging in predicting recurrence. Methods and Materials Intensity modulated RT (IMRT) doses of 66–81 Gy, assigned to patients by the time-to-event continual reassessment method, were delivered over 6 wks with concurrent daily TMZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 30 publications
(27 reference statements)
2
83
1
2
Order By: Relevance
“…The advent of IMRT enables dose distribution that is more conformal to tumoral well as gives permission to dose escalation to target volumes while sparing normal structures [8,9]. Nevertheless, the appearance of distant metastases affects the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of IMRT enables dose distribution that is more conformal to tumoral well as gives permission to dose escalation to target volumes while sparing normal structures [8,9]. Nevertheless, the appearance of distant metastases affects the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is necessary to study further the alternative fraction protocols in patients with GBM. The results of dose escalation have been reported in small, single institution, phase I-II studies (14,15). In these studies, the overall survival has been reported as 20.1 months in patients treated with hypofractioned IMRT.…”
Section: Resultsmentioning
confidence: 99%
“…This may be a great help to the adjustment of the clinical therapy scheme (34) and personalized treatment. In addition, considering the ease of preparation and good imaging qualities, 18 FAlF-NOTA-PRGD2 may be a promising alternative to other RGD agents for PET imaging of integrin a v b 3 expression (14).…”
Section: Discussionmentioning
confidence: 98%